The crisis of distribution : theoretical analysis from economic law - Zhang, Shouwen (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The crisis of distribution is one of the longest standing and complicated issues facing human society. Imbued with social, political, historic, and cultural elements, it varies significantly across different countries as a result of all these factors. As an emerging economy which transferred from a planned to a market economy, China has experienced large distribution gaps since it implemented the Reform and Opening-up Policy in the early 1980s, requiring stronger economic law to mitigate and regulate the crisis of distribution. In this two-volume set, the author analyzes distribution crises from a theoretical perspective before going on to propose law and policy solutions. In this first volume, he discusses the four main concepts and focus points of the crisis of distribution - distribution itself, the crises it faces, the rule of law and development. Concentrating on the major distribution problems China faces in particular, the author proposes regulatory methods which can be used to overcome the distribution dilemma, such as tools from policy and economic law, and reiterates the significance of theory building in resolving the issues. The book should be of keen interest to researchers and students of law, economics, and political science"--
Introduction : distribution crisis and the rule of law -- Distribution pressure and distribution differences -- Relationship and structure of co-integrating distribution -- Legal optimization of distribution structures -- Distribution-orientation based rule of law in economy distribution-oriented rule of law of the economy -- Beyond the distribution crisis : theoretical extension -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Delivery of goods (Law) -- China; Physical distribution of goods -- Law and legislation -- China; Distributors (Commerce) -- Legal status, laws, etc. -- China; LAW / General; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Distribution